Mechanism of Liver Regeneration During ALPPS - Xiao, Yao; Peng, Lantao; Xu, Hongjuan; Huang, Ming; Yang, Chao; Liu, Guodong; Ouyang, Xiwu; Li, Xiaoli; Wang, Yuanjing; Sheng, Langqing; Zhai, Denggao; Lin, Ling; et al. (Frontiers in Cell and Developmental Biology, 2022)
Liver cancer is one of the most lethal malignant tumors in the world, and surgical resection is the main treatment for liver cancer. Liver failure due to insufficient residual liver volume is a fatal complication after hepatectomy. How to effectively increase the residual liver volume after hepatectomy and improve the safety of hepatectomy has always been a problem to be solved in liver surgery. Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) effectively reduces the occurrence of liver failure due to insufficient residual liver volume after hepatectomy, thereby increasing the probability of radical resection by inducing rapid proliferation of residual liver tissue. However, the molecular mechanism of residual liver tissue regeneration after primary ALPPS (combined liver partition and portal vein ligation) remains unclear. Here, we found that lots of circular RNAs (circRNAs) are upregulated after ALPPS in pig liver cell, then, we identified the orthologous circRNA in human and pig to detect their function in liver regeneration. The result showed that loss of circ-0067724 and circ-0016213 can suppress liver cell proliferation. Together, these finding suggest that circ-0067724 and circ-0016213 play an important role in liver cell proliferation, and target this may help us find new strategies to promote liver regeneration.